Penguatan Resiliensi Akademik dan Manajemen Diri Santri Melalui Metode Edugame "The Shield of Faith" di Dayah Al-Muslimun - Khoirunnisya Dalimunthe; Yeni Pita Sari; Nanda Yustina (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2026)
Community service is one of the main pillars of the Tri Dharma of Higher Education, which aims to apply knowledge for the advancement of society. This activity aims to strengthen the academic resilience and self-management skills of students at Dayah Terpadu Al-Muslimun through the interactive edugame method "The Shield of Faith". The implementation method uses a Participatory Action Research (PAR) approach with experiential learning through scenario-based role-playing. The activity took place at Dayah Terpadu Al-Muslimun and was attended by 114 students at the Madrasah Aliyah level. The results showed high enthusiasm from the participants, as evident from active participation during the training sessions and an increased understanding of the concepts of mental resilience and self-management. This activity also served as a platform for multidisciplinary collaboration, enriching the perspectives of community service. In conclusion, strengthening academic resilience and self-management from an early age is highly beneficial in preparing students to face academic and life challenges in the future. Cross-disciplinary collaboration strengthens the positive impact of community service activities. This activity is expected to become a sustainable program and involve more parties in the future.